New Solubility Data of Hydrocarbons in Water and Modeling Concerning Vapor-Liquid-Liquid Binary System - Mokraou, Salim (2007)
Solubility data in water of ethane, propane, isobutane, n-butane, n-pentane, and n-hexane have been obtained as a function of temperature in vapor-liquid-liquid equilibrium (VLLE) conditions. The minimum temperature of experiments is 288 K, while the maximum temperature, for each system, is lower than the critical temperature of the corresponding hydrocarbon. New solubility vs temperature correlations are given herein for the studied hydrocarbons in water. Henry's law and activity coefficients at infinite dilution are deduced from the experimental solubility data. Good agreement is found with available literature data.